(untitled) (Journal of Geography and Environmental Management, 2024)
The problem of shortage of water resources, especially fresh water and runoff during the growing season, is relevant for all countries in arid regions. In Central Asia, including Kazakhstan, mountainous regions are one of the main suppliers of fresh water. The climate-caused degradation of mountain glaciation causes changes in mountain ecosystems, having direct impact to human life, causes changes in hydrological cycles, biogeochemistry of rivers andglacial lakes, affecting the quality and availability of water resources.The article presents the results of the seventy-year monitoring of changes in the area of glaciation of the northern slope of Ile Alatau. According to the satellite surveys of the Landsat 5 TM+ and Landsat 8, 9 OLI TIRS sensors for 1990, 2006, 2014 and 2022, the state of glaciation was assessed. To analyze the degradation of the glacial system wereused the data from previous inventories of this region - as of 1955, 1974, 1979, 1990, 2008.For 67 years, the glaciation of the northern slope of Ile Alatau has decreased in area by 140.4 km2 (by 49%), losing 2.1 km2 or 0.72% of its area per year. The rate of degradation has not changed much in comparison with previous studies of the glaciation of this region. Based on the forecast, by the end of the 21st century, the glaciation of the northern slope of the Ile Alatau may disappear, of course, by the remaining conditions of degradation.